2021
DOI: 10.47441/jkp.v16i1.160
|View full text |Cite
|
Sign up to set email alerts
|

Preferensi Konsumen terhadap Produk Sasirangan di Kota Banjarmasin

Abstract: Sasirangan merupakan kain khas dari Kalimantan Selatan yang kerap kali digunakan pada acara-acara formal, maupun sebagai seragam kantor. Namun seiring dengan berjalannya waktu, kain sasirangan sudah mulai digunakan sebagai pakaian sehari-hari bagi masyarakat di Kalimantan Selatan. Penelitian ini bertujuan untuk menganalisis prefrensi konsumen dalam memilih produk sasirangan. Penelitian ini menggunakan metode deskriptif-eksploratif untuk menggali lebih dalam aspek prefrensi konsumen dalam memilih produk sasiran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…The position of natural dye Sasirangan products as premium products implies this variety's higher price. Study findings indicated that pricing is still a consideration besides consumers' primary preferences for the blend of colors, patterns, comfort, fashion trends, and brand names [12]. The study's respondents prefer either dye kind (natural or synthetic) [12].…”
Section: The Sasirangan Industry In South Borneo Positively Contribut...mentioning
confidence: 86%
See 1 more Smart Citation
“…The position of natural dye Sasirangan products as premium products implies this variety's higher price. Study findings indicated that pricing is still a consideration besides consumers' primary preferences for the blend of colors, patterns, comfort, fashion trends, and brand names [12]. The study's respondents prefer either dye kind (natural or synthetic) [12].…”
Section: The Sasirangan Industry In South Borneo Positively Contribut...mentioning
confidence: 86%
“…Study findings indicated that pricing is still a consideration besides consumers' primary preferences for the blend of colors, patterns, comfort, fashion trends, and brand names [12]. The study's respondents prefer either dye kind (natural or synthetic) [12]. Unfortunately, the study does not include environmental consciousness variables in determining whether Sasirangan should be used with natural or synthetic dyes according to consumer choice.…”
Section: The Sasirangan Industry In South Borneo Positively Contribut...mentioning
confidence: 94%
“…Lubis et al, 2018;Qothrunnada & Takarini, 2023;Risnasari et al, 2021) Perkembangan seni budaya di tanah air terus berkembang, salah satunya adalah industri batik, dalam industry pewarnaan kain yang salah satunya batik, mempunyai ragam turunan yang diminati masyarakat dan disesuaikan dengan kebutuhannya. Di era pembangunan berkelanjutan atau (sustainable development) industri batik terus berkembang dan banyak menggunakan pewarna pewarna, mulai dari pewarna alam dan buatan (Fitria & Yustisya, 2021;Perdana, 2019;Pradana & Fitriyanti, 2021;Subechiana, 2022;Yuniar et al, 2022).…”
unclassified